The effects of zinc and vitamin C supplementation on changes in height for age anthropometry index on stunting aged 24-59 months - Purnamaningrum, Yuliasti Eka; Margono, Margono; Petphong, Vajee (Jurnal Kesehatan Ibu dan Anak, 2019)
Stunting is a physical growth disorder characterized by a decrease in the speed of growth and the impact of nutritional imbalances. Children affected by stunting up to the age of 5 years will be difficult to repair, so it will continue into adulthood and can increase the risk of offspring with low birth weight babies (LBW). Adequacy of zinc and vitamin C for growth is an important factor for children to grow well. This study aims to determine the effect of zinc and vitamin C on changes in the height of age anthropometric index. Methods: (1) A randomized pre-post test with a control group study design with a total of 70 children aged 24-59 months in the work area of ​​ Sentolo II Public Health Center (PHC) and Pengasih II PHC. (2) The provision of zinc and vitamin C as much as 5 mg for 12 weeks in the experimental group and placebo syrup in the control group. Data analysis used chi-square, independent t-test, Mann Whitney, and Spearman. The results showed that zinc and vitamin C supplementation had a significant effect on changes in the height for age anthropometry index (p = 0.001 95% CI 0.13-0.45) with a mean difference of 0.29 and height (p = 0.016 95 % CI 0.14-1.28) with a mean difference of 0.7cm. The effect is greater in children who have a lower height for age index (p = 0.00 r = -0.61). Zinc supplementation and vitamin C significantly affected children's height and height for age index.